The impact of human resource practices and organizational citizenship behaviours on firm performance - Davood, Babaei; Ahmad, Aminah; Idris, Khairuddin; Omar, Zoharah (2009)
The purpose of this study is to investigate the mediation effects of organizational citizenship behaviours in the relationship between selected human resource practices and firm performance expressed in terms of quality of services. In this study human resource practices include reward and performance appraisal practices. To achieve these objectives we tested a mediation model using structural equation modelling procedure to examine if the hypothesized model fit the data well. Data were collected from a sample of 179 branches of two banks in Tehran, Iran. 176 managerial employees, 352 non-managerial employees, and 871 customers participated in this study. The results showed that organizational citizenship behaviours fully mediated the relationship between rewards and quality of services and partially mediated the relationship between performance appraisal practices and quality of services.